Synthesis and characterization of europium doped willemite based glass-ceramics derived from rice husks - Mohamed Khaidir, Rahayu Emilia (2019)
Nowadays, researchers have been working on to produce glass phosphors using waste materials for optical application purpose but lack of study in producing europium (Eu³⁺) doped zinc silicate (Zn2SiO4) glass ceramics derived from rice husk as raw material. Firstly, X-ray fluorescence spectroscopy (XRF) had confirmed white rice husk ash (WRHA) contains 90.926% of silica which suitable to produce zinc silicate glass (ZnO- SiO2). Based on the X-ray diffractometer (XRD) analysis of different glass compositions, 60:40 ratio of zinc oxide (ZnO) against WRHA shows amorphous phase which made it optimum composition to produce Zn2SiO4 glass ceramics. Hence, a study on structural and optical properties with subject to sintering temperature (600-1000°C) and dopant concentration (1-5 wt.%) has been done. XRD revealed the intensity of α-Zn2SiO4 phases become sharper indicating good crystallization as temperature increased but drastically dropped due to structural distortion as dopant was added. Field emission scanning electron microscopy (FESEM) shows the particles have good connectivity due to crystallization when sintered while dopant addition had reduced the surface porosity. Meanwhile, Fourier transform infrared spectrometer (FTIR) analysed at 400-2000 cm⁻¹ wavenumber had revealed that the broad bands of SiO4 were getting narrower due to increase in the crystallinity while the presence of Eu³⁺ dopants had weakened the band by lattice defects. Ultra-violet visible spectroscopy (UV-Vis) analysis in the wavelength range of 220-800 nm shows the absorption at ~250-400 nm were uplifted towards higher wavelength due to crystal growth thus band gap values were decreasing from 4.01 eV to 2.98 eV as temperature increased. However, dopant addition increased band gap values from 3.39 eV to 3.67 eV as absorbance shifted to shorter wavelength due to lattice distortion. Photoluminescence spectroscopy (PL) analysis shows red emission exhibited at wavelength 612 nm due to Eu³⁺ transitions under 400 nm excitation. Therefore, this zinc silicate glass ceramics appeared to be a potential phosphor material for electronic devices.